2014
DOI: 10.1120/jacmp.v15i2.4682
|View full text |Cite
|
Sign up to set email alerts
|

Improved accuracy for noncoplanar radiotherapy: an EPID‐based method for submillimeter alignment of linear accelerator table rotation with MV isocenter

Abstract: Accurate alignment of linear accelerator table rotational axis with radiation isocenter is critical for noncoplanar radiotherapy applications. The purpose of the present study is to develop a method to align the table rotation axis and the MV isocenter to submillimeter accuracy. We developed a computerized method using electronic portal imaging device (EPID) and measured alignment stability over time. Mechanical and radiation isocenter coincidence was measured by placing a steel ball bearing at radiation isoce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 28 publications
0
23
0
1
Order By: Relevance
“…The application of an EPID for quality assurance has continued to expand over the past decade . Results of this study suggest that utilizing the EPID as a tool for more automated linac acceptance testing can reduce the number of high‐priority errors occurring during machine acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…The application of an EPID for quality assurance has continued to expand over the past decade . Results of this study suggest that utilizing the EPID as a tool for more automated linac acceptance testing can reduce the number of high‐priority errors occurring during machine acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…Now radiolucent cranial and body immobilization devices allow photon imaging to verify proper patient position. Therefore, this test has been modified from the use of film with the advent of on‐board imagers as the image acquisition device 21 , 22 , 23 , 24 …”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, using invasive fixation devices to the patient's skull, such as metal frames or rings were essential for patient immobilization and target localization in SRS/SRT treatment of intracranial lesions . However, noninvasive (frameless) SRS/SRT treatment has become a standard procedure owing to the development of image‐guided radiotherapy (IGRT) systems in recent years . Chang et al reported that the accuracy of the patient setup with cone‐beam computed tomography (CBCT) image guidance was comparable to that with frame‐based radiosurgery systems .…”
Section: Introductionmentioning
confidence: 99%
“…6 However, noninvasive (frameless) SRS/SRT treatment has become a standard procedure owing to the development of imageguided radiotherapy (IGRT) systems in recent years. [7][8][9][10] Chang et al…”
Section: Introductionmentioning
confidence: 99%